Methodical approaches to the development of land management projects for the establishment (change) of the boundaries of administrative and territorial units - O. S. Dorosh (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2017)
Status of exacuted works for establishment and change of administrative‐territorial borders of formations in Ukraine is researched. Problems connected with their delineation were analyzed as well as methodical approachesto develop projects for land management for establishment (change) borders of administrative – territorial formations were shown